Smart Living Education for The Community Around The Eco-City Bintaro Jaya Housing Area, Pondok Aren District, South Tangerang - Reno Catelya Dira Oktavia; Mimi Enggriani; Florensia Herienda; Amrullah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Managers and communities in the Eco-City Bintaro Jaya Housing Estates, South Tangerang, face challenges in implementing smart and sustainable living principles in order to build harmonious relationships with the community living around the housing estates. The counselling activity aims to increase awareness of waste management, cleanliness, and maintenance of the quality of parks and green open spaces, as well as to encourage the implementation of harmonious living principles by striving for a clean, healthy, and comfortable environment in a sustainable manner. The counselling began by greeting the invitees, namely 20 adult residents around Jalan Elang, Blok HG, followed by remarks and presentations of material by experts (PKM IPT Lecturer Team). The material was delivered through interactive presentations and questions and answers. The activity continued with practical simulations, such as demonstrations and explanations of environmental maintenance and role play of host ethics, to explain the practical application of knowledge. The counselling carried out by the Trisakti Tourism Institute Lecturer Team at the Eco-City Bintaro Jaya Housing Estates succeeded in increasing participants' understanding of smart living. Although there were initial challenges, namely the lack of structured knowledge about simple environmental management and smart living procedures, all participants after receiving counseling understood the good and correct way of waste management, cleanliness, garden maintenance, and the ethics of welcoming guests. The community is advised to apply the principles of sustainable environmental management and collaborate with related parties to create a cleaner and more harmonious environment